Optimalisasi Kemampuan Guru Melalui Pelatihan Kuis Interaktif Secara Daring Berbasis Teknologi Informasi - Adhy Kurnia Triatmaja; Mentari Eka Wahyuni; Barry Nur Setyanto; Rio Tirta Sudarma; Waznan Fauzi Oktavian (Universitas Muhammadiyah Semarang, 2021)
The use of technology is very important in learning in the pandemic era. Various efforts were made to equip teachers to optimize the use of learning media. One of these efforts is to organize training on making interactive quizzes based on information technology which is held at SMP Negeri 1 Jaten. This training aims to provide insight related to learning media so that teachers are able to improve their abilities in making interactive quizzes and have a good impact on the future learning process. The method used in this training consists of three stages, namely preparation, implementation and evaluation.This training was conducted on May 6 – May 7, 2021 and was attended by 32 teachers for grades VII, VIII and IX consisting of subject teachers. The result of this training activity is that the teacher understands the training material well so that all the information obtained can be directly put into practice. Teachers get material that is very relevant to the needs in the classroom and can support learning activities. In addition, teachers get new insights related to learning media that can be applied in preparing interactive quizzes creatively and innovatively.